Luscious Borneo - Rosman, Nur Azureen; Metan, Siti Aisah; Jumain, Junaidi; Mukti, Kasra; Udai, Marni (2012)
Kuih Lidah is one of the commonly known delicacies of Sabah. This cake originated and was made famous by the Malay-Brunei community living in the district of Papar, specifically Kampung Berundong, which is located on Sabah's eastern coast. Usually, the basic ingredients that are required to make Kuih Lidah are milk, icing powder, sugar and butter. The most common form of packaging for Kuih Lidah is packing in plain plastic bags and sold at stalls, shops and market in neighboring districts. Today, many manufactures produce only one type of Kuih Lidah flavor. Our company came with the idea of producing Kuih Lidahs with a variety of flavours such as strawberry, chocolate, vanilla and sambal while still retaining the original taste of Kuih Lidah. Our aim is to attract potential buyer as well as becoming a pioneer in producing kuih lidah in various flavour so that we are different from the other competitors. Apart from that, we also provide delivery services to every shop that demand our products. We also provide opportunities for customers to evaluate the new taste of our very own kuih cincin.